How just a few makes a lot: Speciation via reticulation and apomixis on example of European brambles (Rubus subgen. Rubus, Rosaceae) - Sochor, Michal; Vašut, Radim J; Sharbel, Timothy F; Trávníček, Bohumil (Molecular phylogenetics and evolution, 2015)
New species are generated by many means, among which hybridization plays an important role. Interspecific hybrids can form isolated evolutionary units, especially when mechanisms increasing viability and fertility, like polyploidy and apomixis, are involved. A good model system to study reticulate evolution in plants is Rubus subgen. Rubus (brambles, blackberries), which only in Europe includes 748 accepted species, out of which only four are sexual diploids and all others are polyploid apomicts. We employed two molecular markers (ITS and cpDNA) to shed light on the evolutionary history of European bramble flora and main processes generating such high species diversity. We distinguished just six ancestral diploids (including two extinct ones) for both markers, which gave rise to all European polyploid accessions, and revealed an extreme reticulation in bramble evolution. We furthermore detected hybridogenous origins and identified putative parents for several taxa (e.g. ser. Nessenses), while in other groups (e.g. ser. Discolores) we could also infer the direction of hybridization. By comparing different cp haplotypes having clear geographic patterns, we hypothesize that the origin of European brambles can be attributed to both Holocene species range expansion and Pleistocene climate fluctuations.
Keywords: molekulární evoluce; Models, Genetic; vznik druhů (genetika); DNA, Ribosomal Spacer; Genetic Markers; Polyploidy; modely genetické; Sequence Analysis, DNA; Brambles; diploidie; Diploidy; Europe; Genetic Speciation; Evropa; Apomixis; DNA, Chloroplast; ledový příkrov; Concerted evolution; apomixie; Ice Cover; DNA chloroplastová; Rubus; Hybridization; fylogeneze; Agamospermy; Hybridization, Genetic; sekvenční analýza DNA; hybridizace genetická; genetické markery; Phylogeny; mezerníky ribozomální DNA; polyploidie; Evolution, Molecular